Mentor for Analytical Thinking in Lithuania - Galinienė, Birutė (Ekonomika, 2007)
It is on February 4, 2007 that Prof. Dr. habil. Stanislovas Martišius celebrates his 70-birthday. The Professor has spent many successful years working in the academic and scientific fields at the Economics Institute at the Lithuanian Academy of Sciences and at the Faculty of Economics at Vilnius University, combining his position as a pedagogue, instigator of social activities and administrator to great acclaim. His scientific activities can be divided into several stages: the period between 1961 and 1976 saw his involvement in scientific research concerning the quantitative economic analysis of production, the development of statistical theory and methods and the application and promotion of these economic methods; while in the second stage, from 1977 to 1981, his scientific work concentrated on social prediction methods, problems in ecomometric prediction and the analysis of dynamic economic processes.Through his many published articles, books and studies Prof. S. Martišius has successfully carried on in the footsteps of A. Rimka, V. Jurgutis and other politicians in the fields of economics, economic statistics and policy, and continued and developed the search for methodical and methodological findings in the fields of economic analysis, statistical indexing and prediction. He was also one of the first to initiate wider research into analytical thinking among Lithuania’s economists. In recognition of these Bnd other merits Prof. S. Manišius was awarded the A. Rimka Memorial Prize.Prof. S. Martišius has worked hard and productively where over his 15 years as Head of the Department of Statistics he has been able to engage the whole collective in focused collaboration towards these goals. Together with colleagues from the Department of Statistics (now known as the Department of Quantitative Methods and Modelling) in the Faculty of Economics at Vilnius University he has produced several studies and textbooks. The main directions Prof. S. Mani!ius has taken his scientific research in over the last decade have been applied statistical theory, economic science methodology and the history of economic thinking in Lithuania. Statistical theory, or empirical social cognition methodology, is the main legacy left by this significant individual in discussions on statistical theory as a methodological science.Prof. S. Martišius has managed to ideally combine his scientific and social involvement with the important role of Head of the Department of Statistics and his enterprising leadership of the Faculty of Economies (12 years). I sincerely wish Prof S. Martišius all the very best in further developing new economic thinking, and in this way further adding to the improvement of the quality of the economy and of people’s standard of living.